Implementation of counted layers for coherent ice core chronology - B. Lemieux-Dudon; L. Bazin; A. Landais; H. Toyé Mahamadou Kele; M. Guillevic; P. Kindler; F. Parrenin; P. Martinerie (Climate of the Past, 2015)
A recent coherent chronology has been built for four Antarctic ice cores and the NorthGRIP (NGRIP) Greenland ice core (Antarctic Ice Core Chronology 2012, AICC2012) using a Bayesian approach for ice core dating (Datice). When building the AICC2012 chronology, and in order to prevent any confusion with official ice core chronology, the AICC2012 chronology for NGRIP was forced to fit exactly the GICC05 chronology based on layer counting. However, such a strong tuning did not satisfy the hypothesis of independence of background parameters and observations for the NGRIP core, as required by Datice. We present here the implementation in Datice of a new type of markers that is better suited for constraints deduced from layer counting: the duration constraints. Estimating the global error on chronology due to such markers is not straightforward and implies some assumption on the correlation between individual counting errors for each interval of duration. We validate this new methodological implementation by conducting twin experiments and a posteriori diagnostics on the NGRIP ice core. Several sensitivity tests on marker sampling and correlation between counting errors were performed to provide some guidelines when using such a method for future dating experiments. Finally, using these markers for NGRIP in a five-core dating exercise with Datice leads to new chronologies that do not differ by more than 410 years from AICC2012 for Antarctic ice cores and 150 years from GICC05 for NGRIP over the last 60 000 years.